The basic principle in solving equations is to get all variable terms on one side of the equal sign and all non variable terms on the other side of the equal sign. This is generally accomplished by doing the opposite operation to a term to move it to the other side. (e.g. if a term is added, you would subtract it to move it to the other side.) See examples below of different type of equation solving.

1. Basic equations:
 x + 3 = 7 2x = 14 x + 3 – 3 = 7 – 3 2x = 14 x = 4 2 2 x = 7
1. Two step equations:
 2x – 5 = 11 2x – 5 + 5 = 11 + 5 2x = 16 2 = 2 x = 8
1. Multi-step equations: First simplify each side of the equation, then move variable terms to one side of the equal sign and all non-variable terms to the other side of the equal sign.
 3x + 5 = 2x – 7 4(x – 3) = 2(3x -4) 3x + 5 – 5 = 2x – 7 – 5 4x – 12 = 6x – 8 3x = 2x – 12 4x – 12 + 12 = 6x – 8 + 12 3x- 2x = 2x – 2x – 12 4x = 6x + 4 x = -12 4x – 6x = 6x -6x + 4 -2x = 4 -2 = -2 x = -2 2x + 3(2x – 4) = 4(3x – 5) + 4 2x + 6x – 12 = 12x – 20 + 4 8x – 12 = 12x – 16 8x – 12 + 12 = 12x – 16 + 12 8x = 12x – 4 8x – 12x = 12x – 12x – 4 -4x = -4 -4 = -4 x = 1
1. Equations with fractional coefficients: First multiple all terms of the equation by the lowest common multiple. Then follow the same steps above. =  = 8x + 9 = 10x – 12 2(x + 3) = 5(2x – 1) + (2)(10) 8x + 9 – 9 = 10x – 12 – 9 2x + 6 = 10x – 5 + 20 8x = 10x – 21 2x + 6 = 10x + 15 8x – 10x = 10x – 10x – 21 2x + 6 – 6 = 10x + 15 – 6 2x = -21 2x = 10x + 9 2 = 2 2x – 10 x = 10x – 10x + 9 x = -21 -8x = 9 2 -8 = -8 x = -9 8 =  =  =  = x2 = -2x + 15 6(x + 2) = 21 +1(x + 2)(x -2) x2 + 2x – 15 = 0 6x + 12 = 21 + x2 -4 (x + 5)(x – 3) = 0 x2– 6x – 12 + 21 – 4 = 0 x = -5 or 3 x2 – 6x +5 = 0 (x – 1)(x – 5) = 0 x = 1 or 5